A pan-African pathogen genomics data sharing platform to support disease outbreaks - Christoffels, A.; Mboowa, G.; Heusden, P. van; Makhubela, S.; Githinji, G.; Mwangi, S.; Onywera, H.; Nnaemeka, N.; Amoako, D.G.; Olawoye, I.; Diallo, A.; Mbala-Kingebeni, P.; et al. (Springer, 2023)
High-income countries have a wealth of genomics expertise that can be rapidly activated to deal with disease threats. African countries should invest in a federated data-management system for genomics epidemiology to deal with such threats better.